PERAN MEDIA RELATIONS DI LEMBAGA PENYIARAN PUBLIK (LPP) RRI SURAKARTA - Pambayun Danang Prasetyo; Maya Sekar Wangi (Solidaritas, 2025)
The development of information and communication technology in the digital erahas changed the media consumption patterns of society, so public broadcastinginstitutions like RRI face significant challenges in maintaining their existence. RRISurakarta, as one of the oldest radio stations in Indonesia, is required to adapt to thedynamics of new media and compete with private media and digital platforms. Inthis context, media relations play an important role in building relationships withthe media, disseminating credible information, and maintaining public trust. Thisresearch aims to analyze the role of media relations at LPP RRI Surakarta using themedia relations theory from Cutlip, Center, and Broom. The method used isdescriptive qualitative with data collection techniques through interviews,documentation, and source triangulation. The results of the study indicate that RRISurakarta's media relations role consists of five main aspects, namely providingaccurate information, bridging.